Anaplasmosis-induced hemophagocytic lymphohistiocytosis. Issue 3 (4th May 2022) - de Jesus, Mikhail; Lopez, Amanda; Yabut, Jevin; Vu, Stephanie; Manne, Madhuri; Ibrahim, Lauren; Mutneja, Rahul
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening inflammatory syndrome of severe immune system activation. It is a diagnostic challenge with high morbidity and mortality. We present a case of HLH due to anaplasmosis infection. A 54-year-old man with chronic obstructive pulmonary disease presented with fever, nausea, vomiting, dyspnea, and arthralgias for 6 days. He had a rapidly progressive clinical decline requiring intubation for acute respiratory failure and dialysis for acute renal failure. He tested positive for anaplasmosis. His workup met criteria for HLH. He was treated with doxycycline and a steroid taper with clinical improvement allowing for extubation and renal recovery. Patients with persistent fevers, hepatosplenomegaly, cytopenias, and hyperferritinemia should be worked up for HLH.